Financial Literacy and Attitudes to Redistribution - Alberto Montagnoli; Mirko Moro; Georgios A. Panos; Robert E. Wright (Institute of Labor Economics (IZA), 2017)
This study combines novel financial-literacy data with measures of attitudes to redistribution from the British Election Study. We find a significant negative relationship between financial literacy and attitudes in favour of government intervention for income redistribution. The effect is robust to several specifications, samples, longitudinal models and instrumental variable regressions. Falsification tests show that these results are independent of generic attitudes towards other types of inequality/discrimination, e.g. based on gender, race or sexual orientation. An inquiry into the mechanisms of the effect indicates that the homo oeconomicus effect does not exert an impact on attitudes to redistribution for the less financially literate.
Keywords: D14; D31; I24; 330; financial literacy; redistribution; inequality; attitudes; Great Britain